Resistance of two temperate Lactobacillus paracasei bacteriophages to high pressure homogenization, thermal treatments and chemical biocides of industrial application - Mercanti, Diego Javier (2012)
Temperate bacteriophages iLp84 and iLp1308, previously isolated from mitomycin C-induction of Lactobacillus paracasei strains 84 and CNRZ1308, respectively, were tested for their resistance to several physical and chemical treatments applied in dairy industry. Long-term survival at 4ºC, -20ºC and -80ºC, resistance to either thermal treatments of 63ºC, 72ºC and 90ºC, high pressure homogenization (HPH, 100 MPa) or classic (ethanol, sodium hypochlorite and peracetic acid) and new commercial sanitizers, namely A (quaternary ammonium chloride), B (hydrogen peroxide, peracetic acid and peroctanoic acid), C (alkaline chloride foam), D (p-toluensulfonchloroamide, sodium salt) and E (ethoxylated nonylphenol and phosphoric acid), were determined. Phages were almost completely inactivated after eight months of storage at 25ºC, but viability was not affected at 4ºC, -20ºC or -80ºC. Both phages tolerated well HPH treatments. Phage iLp1308 showed higher thermal resistance than iLp84, but neither resisted 90ºC for 2 min. Best chemical inactivation was accomplished using peracetic acid or biocides A, C and E, whereas biocides B and D were completely ineffective. These results help to improve selection of chemical agents and physical treatments to effectively fight against phage infections in dairy plants.